An exploration of ‘Gurans' phenomena: The face of Youth Violence in Khayelitsha Township - Mguzulwa, Sisanda Millicent (Department of Social Development, 2023)
Youth violence has been troubling the South African society ever since the country's transition to democracy in 1994. Although the problem has been a countrywide phenomenon, certain provinces and cities, predominantly black inhabited townships in the City of Cape Town, have been most afflicted by the new form of youth violence, code-named ‘Gurans'. Cases of Gurans-related violence first appeared in the City of Cape Town's townships around the year 2000 and have exponentially increased. Of these townships, Khayelitsha has been the most afflicted. While there has been significant scholarly attention to this new form of violence, little has been done to expose the finer grains of the factors that cause the problem. Moreso, little attention has been channelled towards documenting the perspectives and feelings of the perpetrators, victims, school children, community members, and educators working in those communities. Lack of such detailed investigations has derailed its eradication. As such, the aim of this study was to proffer new understandings on how youth-related violence have suddenly morphed into the new Gurans phenomenon and how this has affected the community of Khayelitsha in its entirety. This study therefore highlights the centrality of the theories of Social Identity and Violentisation to analysing and understanding violence among youths in contemporary South Africa. A qualitative research design was applied, involving eight focus group discussions with 106 affected youths, 10 interviews with crew members in Gurans, 5 educators from four different schools in Khayelitsha, and 5 community members of Khayelitsha township. This thesis documents Gurans as a new type of youth violence with specific focus on its meaning, causes, effects, as well as the issues and key players that have been involved in its sustenance. This study culminates in policy implications and initiatives that take on board how the violent youths, families, communities and government must conduct themselves to alleviate the problem. It is further suggested the most critical step necessary in the quest to eradicate the scourge of youth violence from communities is for the society to first understand the personal experiences of youth living in malignant communities, which encourages youth to become violent and to associate with violent groups. Such an approach will help to understand the underlying circumstances on why more youth are turning to violence, why they are devising new methods to mete such violence and as well as the broad effects of the violence.